قرض الإيجار التمويلي كألية مستحدثة لدعم المقاولاتية في الجزائر دراسة حالة: المجمع الجهوي للاستغلال لبنك الفلاحة والتنمية الريفية (أم البواقي) - خالدي, فراح; مهاوة, أمال (جامعة الوادي - University of Eloued, 2020)
Through this study, we aim to assess and analyze the reality of financial leasing in the BADR's regional group for exploitation in Umm El-Bouaghi, as it is a modern mechanism in the financing market in Algeria. To do this, we adopted questionnaire tool that was distributed to study the opinions of the Council’s directors on this mechanism. the study finds that financial leasing is one of the financial innovation mechanisms that support entrepreneurship and interest small and medium enterprises, compared to other sources of financing.
Financial leasing as a new mechanism to support businesses in Algeria- case study of the BADR's Regional Group for Exploitation in Umm El-Bouaghi
مقال
Keywords: finance leasing ; Financial innovation ; Entrepreneurial